La Révolution dans la Liberté : des transformations économiques et sociales à l’époque de la Guerre froide - Élodie Giraudier (Les Cahiers ALHIM)
This article explores the content and the implementation of the Revolution in liberty during the Cold war. In 1964, the Christian-Democrat candidate, Eduardo Frei, won the presidential elections with more than 56 % of the votes. His program is inspired in particular by recommendations of the Jesuits and by technicians of the Economic Commission for Latin America and Caribbean. He intends to respect engagements taken in 1961 in Punta del Este. Complete transformations have to aim first and foremost at young people, women, farmers, workers and pobladores. However, the toughening of the Chilean political scene difficults the application of this vast program of socioeconomic reforms. The changes especially concerned the first part of Frei’s government. The agrarian reform is the most accomplished while it crystallized the tensions and appears in 1970 as unfinished. As other reforms, it failed to assure “thirty years of Christian Democrat government”. Nevertheless, the Christian democracy was able to conquer a political space, at the expense of the right and left. The Revolution in Liberty marks a break in the Chilean history because it was one of the first governments to advocate the political integration of social groups that had been previously excluded.